2015
DOI: 10.1007/s00455-015-9639-9
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing Tablets and Capsules Increases the Risk of Penetration and Aspiration in Patients with Stroke-Induced Dysphagia

Abstract: We evaluated the prevalence of difficulties swallowing solid dosage forms in patients with stroke-induced dysphagia and whether swallowing tablets/capsules increases their risk of penetration and aspiration. Concurrently, we explored whether routinely performed assessment tests help identify patients at risk. Using video endoscopy, we evaluated how 52 patients swallowed four different placebos (round, oval, and oblong tablets and a capsule) with texture-modified water (TMW, pudding consistency) and milk and ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 43 publications
(46 reference statements)
2
36
1
Order By: Relevance
“…Patients post-stroke, who were severely dysphagic during the rehabilitation period (within the last 3 years prior to the study), were invited to a follow-up swallowing function assessment. Severe dysphagia during the subacute phase after stroke was operationalised using the Bogenhausen Dysphagia Score sum of scores (BODS1 and BODS2; Schiele et al, 2015, Starrost et al, 2012). These scores are used by therapists and physicians in the German speaking areas of Europe and show impairments of saliva swallow and food intake in clinical/neurological testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients post-stroke, who were severely dysphagic during the rehabilitation period (within the last 3 years prior to the study), were invited to a follow-up swallowing function assessment. Severe dysphagia during the subacute phase after stroke was operationalised using the Bogenhausen Dysphagia Score sum of scores (BODS1 and BODS2; Schiele et al, 2015, Starrost et al, 2012). These scores are used by therapists and physicians in the German speaking areas of Europe and show impairments of saliva swallow and food intake in clinical/neurological testing.…”
Section: Methodsmentioning
confidence: 99%
“…This test has a sensitivity of 92.7% and a specificity of 66.7%. Further, an assessment concerning the impairment of saliva swallow and food intake was performed based on the Bogenhausen Dysphagia Score [BODS, consisting of BODS1 and BODS2 (Schiele et al, 2015, Starrost et al, 2012) with a maximum sum of scores of 16]. A score between 0 and 2 means no dysphagia and between 14 and 16 means profound dysphagia.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, thinking about medication modification is the most logical option when the patient has difficulty swallowing. Even though this is the practice found in this study, other studies (17,21,22) have shown that modifying tablets (breaking, smashing, crushing or dissolving) and capsules (opening), in addition to resulting in unlicensed use, can be toxic to the patient and decrease the action potential, since some drugs are designed to be absorbed in specific places in the digestive tract.…”
Section: Discussionmentioning
confidence: 76%
“…This is a useful method which enables observation of the pharynx and larynx using actual food without irradiation. This can be used at the bedside as it does not require any large-scale devices [29].…”
Section: Videoendoscopy (Ve)mentioning
confidence: 99%